OPTIMIZATION OF THE ROLE AND FUNCTION OF THE PUBLIC PROSECUTOR IN THE NEW CODE OF CRIMINAL PROCEDURE-BASED CRIMINAL JUSTICE SYSTEM REGARDING ASSAULT CASES RESULTING IN DEATH (A STUDY AT THE PESAWARAN DISTRICT ATTORNEY'S OFFICE) - Benny Karya Limantara; Zahra Lulu Mika Khairunnisyah (RADJA PUBLIKA, 2026)
This study analyzes the optimization of the role and function of the Public Prosecutor in Indonesia's criminal justice system under the New Criminal Procedure Code (Law Number 20 of 2025) in handling assault cases resulting in death. Using a normative-empirical legal approach, the research combines statutory and literature analysis with field data obtained through interviews at the Pesawaran District Attorney's Office. The findings indicate that the New Criminal Procedure Code strengthens the Public Prosecutor's position as dominus litis, enabling active involvement from the investigation stage through enhanced coordination with investigators, joint case conferences, and quality control over investigations. These reforms improve prosecutorial effectiveness, reduce repetitive case-file returns, and support a more integrated criminal justice system. The findings are analyzed using Joseph Goldstein's Criminal Justice System theory, which emphasizes total enforcement, full enforcement, and actual enforcement, as well as Philipus M. Hadjon's Authority Theory and Andi Hamzah's Prosecution Theory. The study concludes that strengthening the authority of the Public Prosecutor under the New Criminal Procedure Code promotes a more effective, accountable, and integrated criminal justice system while ensuring legal certainty, justice, and the protection of human rights in criminal proceedings.